SUPPORT FOR DOWN SYNDROME FAMILIES: NEEDS, EXPECTATIONS, AND FEATURE IDEAS - Masdah, Siti; Meilantika, Ayu Diana; Ramadhaniyati, Ramadhaniyati; Maufiroh, Maufiroh; Syabilla, Aulia Putri; Alya Pratama, Natasya Putri (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2025)
Families are the primary caregivers of children with Down syndrome (DS) and often face complex challenges involving medical, emotional, social, and economic aspects. These challenges require support systems that go beyond clinical care and address psychosocial and practical family needs. This study aimed to identify the needs, expectations, and innovative feature ideas desired by families of children with DS as a foundation for developing comprehensive and sustainable family support systems. This study employed a descriptive mixed-method design, integrating quantitative and qualitative approaches. A total of 156 parents or primary caregivers of children with DS in Indonesia participated through an online survey. Quantitative data were analyzed descriptively, while qualitative data were analyzed thematically to explore family experiences and expectations regarding support features. The findings revealed that the main family needs included educational support (42.95%), parental guidance (28.21%), and emotional and social support (17.31%). Families also suggested various digital-based support features, such as interactive educational modules, online consultations with health professionals, therapy activity scheduling tools, parent community forums, and motivational content. These features were perceived as helpful in improving knowledge, caregiving skills, and emotional well-being. In conclusion, support for families of children with DS should adopt a comprehensive, family-centered, and participatory care model. The utilization of digital technology is considered an effective medium for empowerment, communication, and access to support. This approach is expected to strengthen family resilience, enhance the quality of life of children with DS, and promote inclusive and sustainable family support systems.